Inferring the tectonic history of Northwestern Luzon, Philippines, using coral microatoll records - Tan, Fang Yi (2019)
The Philippines sits in a tectonically complex region, bounded by oppositely-dipping subduction zones to the east and west. The possibility that these megathrusts could generate earthquakes and tsunamis that could potentially devastate thousands of lives and infrastructure is worrying, but our understanding of potential faults has hitherto been limited by the lack of geologic and geodetic data, especially in northwestern Luzon (Megawati, et al., 2008; Ramos & Tsutsumi, 2010; Hsu, et al., 2016). This motivated us to collect data from northwestern Luzon to fill this data gap. Here, I present the relative sea level (RSL) records of microatolls from northwestern Luzon – in particular from the Katipunan Barangay in the province of Ilocos Sur. The Katipunan microatolls (ranging from between ~4000 cal yrs BP to ~6000 cal yrs BP in age) are the only microatolls of their generation. Together, they reveal changes in RSL between ~4000 cal yrs BP and ~6000 cal yrs BP that cannot be explained by glacial isostatic adjustment (GIA) alone. Although we currently do not have sufficient data to distinguish if the RSL fluctuations were tectonically induced or sea-level driven, the fact that either of these would produce starkly different implications for hazard mitigation implores us to carry on further work to better understand the RSL signal we observe at Katipunan, and if this RSL oscillation is unique to that site.